Studi Literatur Penggunaan Smartphone-based Thermal Imaging dalam Pengkajian Perfusi Vascular Perifer: Literature Review on the Use of Smartphone-based Thermal Imaging in Peripheral Vascular Perfusion Assessment - Syafa’atun Mirzanah; Rr.Tutik Sri Hariyati (NERS Jurnal Keperawatan, 2020)
The high prevalence and the serious impact of peripheral arterial disease lead the development of diagnostic tools that could be more efficient and easy to use. This review aims to examine the effectiveness of Smartphone-based Thermal Imaging in assessing peripheral perfusion. Article yielded by inserting spesific keywords to Clinical Key, Science direct, ProQuest, and SAGE Publications databases. The inclusion were fulltext, English-based article and peer-reviewed from 2010 to 2018. 217 articles were identified from the databases and finallly we got five relevant articles. Smartphone-based thermal imaging does not had significant different result with ABI, more precision and more easy to use than thermal imaging camera. This device also can be used as monitoring device compared to Doppler ultrasound and angiography. According SWOT analyses, this device might be implemented in Indonesia. Smartphone-based thermal imaging can be used as noninvasive monitoring device to asses peripheral perfusion in fast and easy ways. Next research should examine the specifity and sensitivity of the device and also the standard protocol in capturing photo and also solve the problem of security issue.